Retarded bone growth in thyroid hormone resistance. A clinical study of a large family with a novel thyroid hormone receptor mutation - Kvistad, PH; Lovas, K; Boman, H; Myking, OL (European journal of endocrinology, 2004)
OBJECTIVE: Thyroid hormone resistance (RTH) is characterised by variable tissue hyporesponsiveness to thyroid hormone. The disorder is usually caused by mutations in the thyroid hormone receptor beta (TR beta). We describe a large family with this disorder. SUBJECTS AND MEASUREMENT: We identified 36 family members with RTH in four generations by screening relatives of patients with the diagnosis. The diagnosis was verified by identification of a mutation in the thyroid hormone receptor beta (TR beta) gene. Symptoms, clinical findings and laboratory tests of 29 affected individuals were compared with those of 16 first-degree relatives. RESULTS: Bone maturation in children with RTH was delayed. The height was lower both in children and in adults with RTH than in the controls. Children with RTH had lower birth weight than the controls, particularly when the condition was inherited from the father. We did not observe increased prevalence of neuropsychological symptoms associated with RTH in this family. Palpitations and increased pulse rate indicated mild cardiac hyperthyroidism. Direct sequence analysis of the TR beta gene revealed a novel point mutation, a heterozygous transition c.1031G>C in exon 9 theoretically substituting Gly344Ala. CONCLUSIONS: We found evidence of skeletal tissue hypothyroidism that resulted in permanent growth retardation from prenatal to adult life. We found substantial variations in thyroid hormone levels and clinical presentation, but most individuals were without symptoms of thyroid disorder.